Natural bone fragmentation in the blind cave‐dwelling fish, Astyanax mexicanus: candidate gene identification through integrative comparative genomics. Issue 1 (8th July 2015) - Gross, Joshua B.; Stahl, Bethany A.; Powers, Amanda K.; Carlson, Brian M.
SUMMARY: Animals that colonize dark and nutrient‐poor subterranean environments evolve numerous extreme phenotypes. These include dramatic changes to the craniofacial complex, many of which are under genetic control. These phenotypes can demonstrate asymmetric genetic signals wherein a QTL is detected on one side of the face but not the other. The causative gene(s) underlying QTL are difficult to identify with limited genomic resources. We approached this task by searching for candidate genes mediating fragmentation of the third suborbital bone (SO3) directly inferior to the orbit of the eye. We integrated positional genomic information using emerging Astyanax resources, and linked these intervals to homologous (syntenic) regions of the Danio rerio genome. We identified a discrete, approximately 6 Mb, conserved region wherein the gene causing SO3 fragmentation likely resides. We interrogated this interval for genes demonstrating significant differential expression using mRNA‐seq analysis of cave and surface morphs across life history. We then assessed genes with known roles in craniofacial evolution and development based on GO term annotation. Finally, we screened coding sequence alterations in this region, identifying two key genes: transforming growth factor β3 ( tgfb3 ) and bone morphogenetic protein 4 ( bmp4 ). Of these candidates, tgfb3 is most promising as it demonstrates significant differential expression across multiple stages of development, maps close (<1 Mb) to the fragmentation critical locus, and is implicated in a variety of other animal systems (including humans) in non‐syndromic clefting and malformations of the cranial sutures. Both abnormalities are analogous to the failure‐to‐fuse phenotype that we observe in SO3 fragmentation. This integrative approach will enable discovery of the causative genetic lesions leading to complex craniofacial features analogous to human craniofacial disorders. This work underscores the value of cave‐dwelling fish as a powerful evolutionary model of craniofacial disease, and demonstrates the power of integrative system‐level studies for informing the genetic basis of craniofacial aberrations in nature.